(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The irrigation project is considered one of the important projects in Iraq, as the study area is one of the important agricultural areas, which mostly depends on groundwater wells as well as surface water from the Kirkuk Irrigation Project. This study aims to estimate the irrigation project for drinking, agriculture, and irrigation purposes. (46) Water samples were collected in humid and dry seasons in (2023-2024) and analyzed; several methods and classifications were used, including comparison with Canadian standards, Piper hydrochemical facies classification, and classifications for irrigation purposes. The major and minor elements and heavy metals were analyzed. The physical properties were measured, including pH, electrical conductivity, total dissolved solids, turbidity, and total hardness. It indicates that the Piper scheme of the hydrochemical facies is calcium-magnesium-bicarbonate. The results show, according to the Canadian water quality index, that the water is poor and unsuitable for human use, and does not have an excellent water condition due to turbidity and calcium concentration, pH, and magnesium values exceeding the permissible limit according to WHO and IQS, so it is considered unsafe for drinking. The results show, according to the classifications of SAR, MH, %Na, SP, salinity hazard, and Wilcox, that the study area is generally suitable and good for irrigation and agricultural uses for most soils and agricultural crops. Analyzed Pearson’s correlations in some of the studied parameters in both seasons reveals that the correlation coefficient is strong and significant positive and negative.